2011
DOI: 10.1016/j.biopsych.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Treatment Prevents Delayed Effects of Early Life Stress in Rats

Abstract: Background Early developmental insults can cause dysfunction within parvalbumin (PVB)-containing interneurons in the prefrontal cortex. The neuropsychiatric disorders associated with such dysfunction might involve neuroinflammatory processes. Cyclooxygenase-2 (COX-2) is a key mediator of inflammation and is therefore a potential target for preventive treatment. Here, we investigated whether the developmental trajectories of PVB expression and COX-2 induction in the prelimbic region of the prefrontal cortex are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(177 citation statements)
references
References 80 publications
(102 reference statements)
13
159
4
1
Order By: Relevance
“…The cytotoxic stress generated might block the phosphorylation cascades and affect the kinases that inhibit NFkB and in the end decrease the levels of proinflammatory cytokines to a second challenge. Further studies using the double hit (MS-LPS) model followed by the administration of antidepressive [63] or antiinflammatory substances [64] could help to address the contribution of specific mediators and the timing of the responses to microglial cells and cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic stress generated might block the phosphorylation cascades and affect the kinases that inhibit NFkB and in the end decrease the levels of proinflammatory cytokines to a second challenge. Further studies using the double hit (MS-LPS) model followed by the administration of antidepressive [63] or antiinflammatory substances [64] could help to address the contribution of specific mediators and the timing of the responses to microglial cells and cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, rodent pups separated from their mothers later showed more depressive-like symptoms and lower prefrontal cortex parvalbumin levels (a GABAergic marker) compared to unchallenged pups (Leussis et al, 2012), and these differences were reduced by the administration of an anti-inflammatory cyclo-oxygenase 2 (COX-2) inhibitor (Brenhouse and Andersen, 2011b) or anti-inflammatory IL-10 (Wieck et al, 2013). More indirectly, physical exercise and anti-depressant medications have antiinflammatory effects (Gleeson et al, 2011;Hannestad et al, 2011) and they have both appeared to buffer the effects of early-life stress on brain and behavioral outcomes (Harrison and Baune, 2014).…”
Section: Reversibilitymentioning
confidence: 99%
“…First, higher baseline levels of inflammation have been associated with greater stress-induced responses in animal models (Hodes et al, 2014) and humans (Eraly et al, 2014;Michopoulos et al, 2015). Second, administration of anti-inflammatory agents, such as COX-2 inhibitors or IL-10, can buffer the expression of biological and clinical sequelae of early-life stress in rodents, including the reduction in prefrontal cortex parvalbumin levels and the onset of depressive-like symptoms (Brenhouse and Andersen, 2011b;Wieck et al, 2013). Third, non-pharmacological strategies with anti-inflammatory properties, physical exercise, and anti-depressant medications, can buffer the effects of earlylife stress on brain and behavioral outcomes in animal models (Harrison and Baune, 2014).…”
Section: Reversibilitymentioning
confidence: 99%
“…[36][37][38] Ultimately, interneuron dysfunction could contribute to altered sensory perception, 39 deficits in working memory, 18,40 attention, 41 and learning. 42 Recent studies have revealed anomalies in hippocampal and/or prefrontal PVI in many preclinical animal models aiming to reproduce genetic vulnerabilities [43][44][45][46] or environmental risk factors 47 such as prenatal maternal stress, 48 maternal and perinatal immune challenge, 49,50 hypoxia, 51,52 early-life iron deficiency, 53 maternal separation, 54 and social isolation. 55,56 Similarly, nongenetic developmental models also result in altered prefrontal PVI.…”
Section: Pvi/pnn Impairmentmentioning
confidence: 99%